SEJARAH ADAT PENGANTIN PONOROGAN DI KABUPATEN PONOROGO TAHUN 2008-2019 - Pratama, Kristian Aji (Historia, 2023)
This thesis examines the history of Ponoragan wedding customs in Ponorogo Regency in 2008-2019. The purpose of this study is to explain the history of the formation to the inauguration of the Ponoragan bridal custom in Ponorogo Regency and the existence of the Ponoragan bridal custom after it was nationally confirmed by the Central Leadership Council of the Indonesian Bridal Makeup Expert Association (HARPI) "MELATI" in 2017. The method used in this study is a historical method consisting of heuristics, source criticism, interpretation, and historiography. The approach used is cultural anthropology with anthropological theory in socio-cultural dynamics put forward by Kingsley Davis. The results of this study indicate that the Ponoragan bridal custom is a new cultural identity inspired by several iconic elements found in Ponorogo Regency, especially the Reyog Ponorogo Art. The early formation of the Ponoragan wedding tradition was inseparable from the influence of Mataraman culture, namely Solo and Yogyakarta. Prior to the existence of the Ponoragan wedding custom, the Ponorogo people wore Solo and Yogyakarta wedding customs. After 2008 the wedding customs used by the Ponorogo people were the Ponoragan wedding customs, the Modern wedding customs, and the Sunda Siger wedding customs. In 2008 Sutji Hariati who was chairman of the HARPI "MELATI" Ponorogo District Leadership Council had aspirations to create a regional bridal custom typical of Ponorogo Regency, then the idea was discussed in monthly meetings with the management of the HARPI "MELATI" Ponorogo District Executive Board with an agenda Excavation of traditional bridal traditions from the Ponorogo Regency area. The Ponoragan bridal custom was nationally confirmed by the HARPI Central Leadership Council "MELATI" in 2017 and won second place in the national level traditional bridal make-up event in the city of Bandung in 2019. Keywords: Ponoragan Bridal Tradition, Reyog, Mataraman